Design and Performance Test of Brown Rice Germinator with Automatic Environmental Control System for Production of Germinated Brown Rice - Ressy Angli Permatasari; Sutrisno Sutrisno; I Wayan Budiastra; Haris Mawardi; Angga Firmansyah; Arfandi Hermawan; Elisa Eka Ari Purwanti Ningsih (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
A germinator equipped with automatic environmental control system has been developed to produce the high quality of germinated brown rice. The germinator consists of germination chamber, temperature and relative humidity sensors, relays, actuator, and display panel so the germination process can be set up and controlled. The performance test were carried out covering the technical reliability of the system and the capability of germinator to produce germinated brown rice. The test results show that the brown rice germinator with an automatic environmental control system worked very well. The use of water misters and PTC air heaters is able to maintain humidity and air temperature inside germinator. The brown rice germinator can produce germinated brown rice with germination rate more than 80%. The result shows that the brown rice germinator can be used to produce germinated brown rice both for private and commercial use. Keywords: Brown rice, Germination, Humidity, Temperature.